Between Punishing Enemies and Educating Workers: Adoption of the Soviet Legal Category of khuliganstvo in Czechoslovakia and in the German Democratic Republic, 1956–1977 - Kotalík , Matěj (Dějiny – teorie – kritika, 2015)
This contribution presents a comparative study of adoption of the normative Soviet term khuliganstvo in Czechoslovakia and the GDR. The comparison uses a notion of intercultural transfer. The adoption of this normative concept and its application, which resulted in the Czechoslovak notion of výtržnictví (hooliganism) and East German notion of Rowdytum, is traced as creating a mixture of the Soviet influence and the local tradition. In part, this could be seen as due to the term’s evolution in its country of origin, since in the newly post-Stalinist Soviet Union, the meaning of khuliganstvo was being debated and re-assessed. In the GDR, moreover, immediately after 1956, the Polish influence that was dominant, later weakened and was replaced by the Soviet one. Soviet influence can be traced in the way ‘disrespect’, the main component of both legal norms, was treated. In both Czechoslovakia and the GDR, a more critical and independent approach prevailed, but awareness of the Soviet model inspired various amendments and suggestions, both implemented and not implemented, which aimed at improving dissatisfactory legal practice in the relevant country. In the light of empirical facts based on the transfer (Transfervergleich), we suggest a possible theoretical extension of the existing notion of intercultural transfer.